Entrepreneurship Learning for Early Childhood in Early Childhood Institutions - Waluyo, Edi; Latiana, Lita (Universitas Negeri Semarang, 2014)
Entrepreneurial learning in early childhood is carried out by involving children in learning activities that exist in the class. Through the involvement of children in learning activities, children will know what steps should be taken to instill the values of entrepreneurship. So with entrepreneurial learning, values such as responsibility, creativity, and capability of making a decision will appear on the child when stimulated early. This research was conducted in early childhood institutions in Gunungpati Subdistrict, Semarang. The research result shows the development of entrepreneurial learning during learning programs in early childhood education institutions, students were introduced to various entrepreneurial values that correspond to the potential of children and provide them with early support for their skills.How to citeWaluyo, E., & Latiana, L. (2014). Entrepreneurship Learning for Early Childhood in Early Childhood Institutions. Indonesian Journal Of Early Childhood Education Studies, 3(1), 59-64. doi:10.15294/ijeces.v3i1.9478